Analisis Flaypaper Effect Pada Dana Alokasi Umum, Dana Alokasi Khusus, Dana Bagi Hasil, dan Pendapatan Asli Daerah Terhadap Belanja Daerah(Studi Empiris pada Kabupaten/Kota Wilayah Jawa Tengah Tahun 2012-2014) - Fauziyah, Rini; , Dra. Mujiyati,M.Si (2017)
This research is meant to give empirical evidence whether General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund and Local Own Source Revenue have influence to the expenditure in sub-districts/citiesin Java Province. And to give empirical evidence whether the flaypaper effect occurs in 2012-2014. Sample of this research amount to 20 regencies and 5 cities in Central Java Province. In this research used multiple regression analysis. Result of this research shows that DAK, PAD influence significant statistic with local expenditure at the 0.05 rate of significancy and DAU, DBH not influence significant with local expenditure it also proves that the flaypaper effect does not occur in the area with a high Local Own Source Revenue or in a low Local Own Source Revenue.